Treatment Satisfaction with Flexible-dose Fesoterodine in Patients with Overactive Bladder who were Dissatisfied with Previous Anticholinergic Therapy: A Multicenter Single-Arm Clinical Study - Choi, Jin Bong; Cho, Kang Jun; Park, Won Hee; Lee, Dong Hwan; Kim, Young-Ho; Cho, In Rae; Yoon, Hana; Kim, Young Sik; Kim, Joon Chul (Urology Journal, 2020)
Purpose: We investigated treatment satisfaction with flexible-dose fesoterodine in patients with overactive bladder (OAB) who were dissatisfied with previous anticholinergic therapy. Materials and Methods: The subjects were prescribed fesoterodine 4 mg for 4 weeks and fesoterodine 4 mg or 8 mg for another 8 weeks. The primary end point of this study was patients’ satisfaction after 12 weeks of fesoterodine treatment on a five-point Likert scale. Secondary end points included a change in the number of daytime micturition, urgency incontinence episodes, urgency episodes, and nocturnal micturition in a 24-hour period from baseline to final assessment. Results: Overall, 84 patients were assigned to the treatment group in this study and 63 patients completed the 12-week treatment course. A final fesoterodine dose of 4 mg and 8 mg was used by 45 (71.4%) and 18 (28.6%) patients, respectively. The satisfaction and dissatisfaction rates at 12 weeks were 69.9% and 14.2%, respectively. Mean changes in the daytime micturitions (9.73 ± 4.72 vs. 7.76 ± 2.86), urgency episodes (7.73 ± 5.68 vs. 3.71 ± 4.09), and nocturnal micturitions (2.13 ± 1.36 vs. 1.68 ± 1.12) in 24 hours improved significantly with flexible-dose fesoterodine treatment (P < .05). Most adverse events were mild and none were severe. Conclusion: The flexible dose fesoterodine represents an alternative treatment modality in patients with OAB who are dissatisfied with previous anticholinergic therapy in Korea.